Measuring Health Workers Perspectives of Patient Safety Culture in Indonesian Hospital Using HSOPSC - Dewi Mulyawati, Sita; Setyaningsih, Yuliani; Maher Denny, Hanifa (Journal of Educational, Health and Community Psychology, 2025)
Patient safety is a critical component of healthcare quality, with an increasing emphasis on cultivating a strong safety culture within healthcare organizations. A robust safety culture is linked to improved patient outcomes, particularly in hospital settings. This study contributes to the international literature by examining the perceptions of safety culture among healthcare professionals in Indonesia through a cross-sectional survey involving 100 health workers using the Hospital Survey on Patient Safety Culture (HSOPSC) instrument. Descriptive and inferential statistics were employed to analyze the data, revealing that the dimension of organizational learning and continuous improvement received the highest positive response rate (83%), while teamwork across hospital units was notably low at 43.8%. Multiple regression analysis revealed that organizational learning and continuous improvement was the most significant predictor of overall safety perceptions (β = 3.975, p = 0.000), emphasizing the importance of sustained learning in fostering a robust safety culture. This study highlights the need for structured training programs on teamwork and error reporting without penalty, advocating for enhanced healthcare policies in Indonesia to strengthen patient safety culture.